Mengetahui Kualitas Briket Cangkang Kelapa Sawit Menggunakan Perekat Arpus sebagai Energi Alternatif - Azhar Basyir Rantawi (JURNAL CITRA WIDYA EDUKASI, 2019)
Palm shell biomass has a very large amount. This can be found in the processing of palm fruit into palm oil, 60% of the palm shells produced in each process of making palm oil. With such a large amount, palm oil shells can be used as an energy source that can be used daily. This study purpose to compare the quality of oil palm shell charcoal briquettes with the quality of briquettes from the Indonesian National Standard. The making of briquettes in this study uses the low compaction method using a binder. The binder used in the manufacture of briquettes is arpus. Some things that become the assessment parameters include heat value, moisture content, ash content and time of combustion. The results showed that the calorific value produced was 6,366 kcal/kg, the resulting water content was 5.5%, the ash content produced was 7.11%, and the burning time was 92.3 minutes. The quality values ​​produced by palm shell charcoal briquettes using arpus fuel have better quality values ​​than the Indonesian National Standard (SNI No.1 / 6235/2000).